The Agglomeration of the Hotel Industry and Its Impact on Socio-Economic Structure in North Lombok Regency - Honey Alya; Iwan Harsono; Muhamad Bai'ul Hak (LP2M IAIN Palopo, 2026)
This study analyzes the impact of the hotel industry agglomeration on the socioeconomic structure of communities in North Lombok Regency, focusing on Sigar Penjalin Village and Gili Indah Village. Using a descriptive qualitative approach supported by simple quantitative data, this study involved 47 respondents selected through purposive and quota sampling. The results indicate a massive structural shift in livelihoods, with 55.32% of respondents now working in the hospitality sector—a sharp increase from the initial situation, which was dominated by the primary and informal sectors. Economically, average household income has increased significantly, by 190% in parts of Sigar Penjalin Village and 121.4% in Gili Indah Village, although the distribution of benefits is uneven among individuals. From a social perspective, 85.11% of respondents reported an increase in their ability to finance their families’ education; however, there were pressures in the form of rising land prices, changes in lifestyle, and reduced access to the beach. In the fiscal dimension, the contribution of hotel taxes to the Regional Revenue (PAD) of North Lombok Regency has increased consistently from 21.50% (2019) to 32.62% (2025). This study concludes that the agglomeration of the hotel industry drives tangible yet uneven socioeconomic transformation, necessitating inclusive policies such as vocational training, strengthened spatial planning regulations, and accelerated development of educational infrastructure in tourist areas. Keywords: Agglomeration, Hotel Industry, Socio-economic Structure, North Lombok